Relationships between follicular fluid steroid concentrations and uterine infections in ovarian cystic cows. (July 2016) - Heidari, Mehdi; Kafi, Mojtaba; Khodakaram-Tafti, Azizollah; Derakhshandeh, Abdollah; Mirzaei, Abdollah
Abstract The present study aimed to determine the relationships among uterine bacterial infection, ovarian cysts, and endometritis. A total of 21 genital tracts with ovarian cysts were collected from the abattoir. Cystic fluids were aspirated from ovarian cysts (follicular cysts, n = 10; luteal cysts, n = 11) and eight large follicles (<15 mm) with clear appearance as control for hormone assay. Samples from the internal surface of the uterine body, right and left uterine horns were collected and cultured for bacteriological examinations. In addition, samples from the cystic walls, uterine horns, and bodies were subjected to histopathological examinations. E2 /P4 ratio was higher in follicular fluid in cows without ovarian cysts but with endometritis than that of cows with both ovarian cysts and endometritis (3.47 ± 1.37; 0.25 ± 0.11, p = 0.004). Further, cows that had endometritis and no ovarian cyst had a higher E2 /P4 ratio than those of endometritic cows with either follicular cyst (3.47 ± 1.37; 0.51 ± 0.17, p = 0.03) or luteal cyst (3.47 ± 1.37; 0.003 ± 0.002, p = 0.01). As the E2 /P4 ratio increased, the numbers of isolated bacterial species decreased from nine to one species of bacterial isolates. In conclusion, as the E2 /P4 ratio increased in the follicular fluid, the numbers and diversity of bacterial species significantly decreased irrespective of pathogenicity of the uterine bacteria.